A shock front at the radio relic of Abell 2744 - Eckert, Dominique; Jauzac, M.; Vazza, F.; Owers, M. S.; Kneib, J.-P.; Tchernin, Céline; Intema, H.; Knowles, K. (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. Radio relics are Mpc-scale diffuse radio sources at the peripheries of galaxy clusters which are thought to trace outgoing merger shocks. We present